Economic usefulness of older workers in terms of productivity in the modern world - Janis Kudins (Insights into Regional Development)
Along with the modern phenomenon of population aging, economists are also concerned about a shift in the composition of the workforce from relatively young to relatively old workers. This study is aimed to empirically prove the hypothesis that in the modern world the economic usefulness of older workers in terms of productivity is determined, in addition to the characteristics of the elderly workforce, by factors characterizing the level of territory development. The theoretical background and methodology of this study is formed on the basis of the concept of “specific human capital” by G. Becker and the conception of endogenous growth. The author uses the latest statistics for 63 countries of the world and several methods of quantitative data analysis: correlation analysis, regression analysis and cluster analysis – in order to detect not only correlational parallelism, but also causal relationships between the variables included in the proof of the research hypothesis. The results of the empirical analysis show that technological readiness, along with a high level of lifelong learning in the country, are the catalysts that ensure the economic usefulness of older workers in terms of productivity in the countries of the modern world. The author also concludes that a baseless raising the retirement age in the country, without considering the above factors that characterize the level of development of this country in technological and learning aspects, does not allow the effective use of the economic potential of older workers.